2022
DOI: 10.1039/d2tc02121h
|View full text |Cite
|
Sign up to set email alerts
|

The role of the commercial nucleating agent HPN-68L in the stretchable and electrical properties of solvent vapor annealed P3HT

Abstract: Crystallinity, molecular order and tie chains are crucial factors in determining the mechanical and electrical properties of semiconducting polymers. 1,2-Dichlorobenzene (ODCB) vapor annealing increases the crystallinity and molecular order but...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…The annealing method was described in detail in other work of our lab. 25 Ultrasonicated P3HT films. A desired weight of P3HT solid (M w = 7.4 Â 10 4 g mol À1 ) was dissolved in toluene and stirred at 60 1C overnight.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The annealing method was described in detail in other work of our lab. 25 Ultrasonicated P3HT films. A desired weight of P3HT solid (M w = 7.4 Â 10 4 g mol À1 ) was dissolved in toluene and stirred at 60 1C overnight.…”
Section: Sample Preparationmentioning
confidence: 99%
“…In P3HT5-90-80, which has the best conductivity and mobility, an interpenetrating network morphology forms. This interpenetrating network morphology is similar to that observed in our previous work, which has been indicated to benefit high conductivity and COS. 28 With the increase in the ODCB content, namely, in the P3HT5-80-80 ultrathin film, an interpenetrating network morphology can also be observed. These AFM images indicate that the addition of HPN-68L and the application of ultrasonication benefit the formation of interpenetrating network structures in the P3HT ultrathin films.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…In our previous work, we found that the commercial nucleating agent bicyclo[2.2.1]heptane-2,3-dicarboxylic acid disodium salt (HPN-68L) was a nucleating agent of poly(3hexylthiophene) (P3HT). 28 The addition of HPN-68L increases the number of nucleation sites in P3HT and accelerates P3HT crystallization, effectively bridging the crystals and increasing the number of tie chains in P3HT films, which benefits carrier transport and stretchability. For P3HT above a certain molecular weight, the addition of HPN-68L can improve the conductivity without significantly reducing the crack onset strain (COS) when the P3HT film is annealed by 1,2-dichlorobenzene (ODCB) vapor, which solves the difficult problem of the low ductility of annealed P3HT films.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation